Synthesis and Investigation of Phthalazinones as Antitubercular Agents. Issue 8 (13th February 2019) - Santoso, Kristiana T.; Cheung, Chen‐Yi; Hards, Kiel; Cook, Gregory M.; Stocker, Bridget L.; Timmer, Mattie S. M.
Abstract: A series of 2‐ and 7‐substituted phthalazinones was synthesised and their potential as anti‐tubercular drugs assessed via Mycobacterium tuberculosis (mc 2 6230) growth inhibition assays. All phthalazinones tested showed growth inhibitory activity (MIC <100 μm ), and those compounds containing lipophilic and electron‐withdrawing groups generally exhibited better anti‐tubercular activity. Several lead compounds were identified, including 7‐((2‐amino‐6‐(4‐fluorophenyl)pyrimidin‐4‐yl)amino)‐2‐heptylphthalazin‐1(2 H )‐one (MIC=1.6 μm ), 4‐tertbutylphthalazin‐2(1 H )‐one (MIC=3 μm ), and 7‐nitro‐phthalazin‐1(2 H )‐one (MIC=3 μm ). Mode of action studies indicated that selected pyrimidinyl‐phthalazinones may interfere with NADH oxidation, however, the mode of action of the lead compound is independent of this enzyme. MIC=minimum inhibitory concentration. Abstract : A library of phthalazinones was synthesised and screened for antituberculosis activity. All phthalazinones inhibited mycobacterial growth (MIC<100 μm ), with the lead compound, 7‐((2‐amino‐4‐(4‐fluorophenyl)pyrimidin‐4‐yl)amino)‐2‐heptylphthalazin‐1‐(2 H )one exhibiting an MIC value of 1.6 μm . Mode of action studies suggest that some phthalazinones interact with the respiratory chain to cause dysregulation of NADH oxidation.